Inference of Choice Sets: Application to Grocery Retailing - Anna Lu (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In the empirical literature on grocery retailing it is typically assumed that all consumers choose from the full set of products in the market. We develop an approach to formally test this assumption. Our test can be applied to individual-level purchase data. Unlike previous approaches it does not require stated data on choice sets; instead, it relies on only widely available cost shifter data. We show an application to the German retail market for milk and find that the model of homogeneous, full choice sets is outperformed by a model in which consumers consider only the products of the retailer they are currently shopping in.
Keywords: L00; D12; L13; 330